2021
DOI: 10.3390/f12121741
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Biosecurity-Based Accreditation in the Plant Trade: A UK Example

Abstract: It is widely acknowledged that a major threat to tree health biosecurity comes from trade, particularly through the importation of containerised live plants and associated growing media. Nurseries can collectively play a key role in mitigating pests and diseases through attention to their daily practices (e.g., procuring plants, storage and management). More widespread adoption of best practices in the sector could be promoted through the introduction of a UK-wide accreditation scheme. However, the success of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…This suggests an economic angle, which is in line with previous studies with horticulturalists (Marzano et al, 2017), potato and wheat growers (Ilbery et al, 2012), and plant nurseries (Marzano et al, 2021), which found that concerns about economic impact of biosecurity measures can hinder professionals' willingness to adopt them. Further, results from Marzano et al (2021) suggest that another barrier is a perception that their individual action may be ineffective or put them at a competitive disadvantage if collective implementation of biosecurity measures by sector operators does not take place.…”
Section: C2 Plant Health Stakeholders and The Plant Passportsupporting
confidence: 86%
“…This suggests an economic angle, which is in line with previous studies with horticulturalists (Marzano et al, 2017), potato and wheat growers (Ilbery et al, 2012), and plant nurseries (Marzano et al, 2021), which found that concerns about economic impact of biosecurity measures can hinder professionals' willingness to adopt them. Further, results from Marzano et al (2021) suggest that another barrier is a perception that their individual action may be ineffective or put them at a competitive disadvantage if collective implementation of biosecurity measures by sector operators does not take place.…”
Section: C2 Plant Health Stakeholders and The Plant Passportsupporting
confidence: 86%
“…With regards to gardeners, the authors reported that from the few evidence available "the main finding appeared to be high levels of relatively superficial knowledge" 68 . Marzano et al (2021), recently investigated nurseries' awareness while testing the appetite for a hypothetical accreditation scheme for UK plant nurseries. Through semi-structured interviews with nurseries (N=19) and consumers (N=22), the authors found increasing awareness about plant health among plant growers and traders, and consumers.…”
Section: Levels Of Awarenessmentioning
confidence: 99%
“…The studies explored awareness of plant health issues and risk perception in different stakeholder groups. Some studies focused on the general public (Fuller et al 2017;Eriksson et al 2018;Quin et al, 2020;Jepson et al 2017;Hilaire et al, 2022;Urquhart et al 2017) and multi-stakeholder groups (Marzano et al 2015;Marzano et al, 2016;Marzano et al 2017;Urquhart et al, 2019), others looked at the level of awareness in specific populations: plant-buyers (Dunn et al 2020); tourists (Melly and Hanrahan, 2020); nurseries (Marzano et al, 2021); air and see travellers (Pace et al, 2022); land managers (Marzano et al, 2020); and farmers (Ilbery et al, 2012;Makgoba et al, 2021;Mkenda et al, 2020;Kansiime et al, 2020).…”
Section: Descriptive Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Plant diseases can cause considerable ecological, economic, and social impacts (Freer-Smith & Webber 2017;Hill et al 2019;Mitchell et al 2022). The awareness of their potential impact is increasing in the horticulture and forestry sectors (Marzano et al 2021) but in habitats, outside of woodlands, plant diseases are rarely considered (Mitchell 2023). Plant diseases are defined here as the plant health consequences of biotic agents, that is, pests and pathogens, referred to as pests throughout.…”
Section: Introductionmentioning
confidence: 99%